2014
DOI: 10.1371/journal.pone.0106625
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia Is a Result, Rather than a Cause, of Depression under Chronic Stress

Abstract: BackgroundAlthough the accumulation of homocysteine (Hcy) has been implicated in the pathogenesis of depression, whether Hcy is directly involved and acts as the primary cause of depressive symptoms remains unclear. The present study was designed to clarify whether increased Hcy plays an important role in stress-induced depression.ResultsWe employed the chronic unpredictable mild stress model (CUMS) of depression for 8 weeks to observe changes in the plasma Hcy level in the development of depression. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Furthermore, the beneficial effects of B 12 supplementation on hyperhomocysteinemia in aged rats have confirmed the importance of cobalamine in methionine metabolism in the brain (46). Although, numerous studies have pointed to the key role of hyperhomocysteinemia-induced neurotoxicity in various brain regions, recent research has presented the crucial possibility that hyperhomocysteinemia may be just a result of, rather than a cause of, at least some mood disorders, such as depression under chronic stress (47).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the beneficial effects of B 12 supplementation on hyperhomocysteinemia in aged rats have confirmed the importance of cobalamine in methionine metabolism in the brain (46). Although, numerous studies have pointed to the key role of hyperhomocysteinemia-induced neurotoxicity in various brain regions, recent research has presented the crucial possibility that hyperhomocysteinemia may be just a result of, rather than a cause of, at least some mood disorders, such as depression under chronic stress (47).…”
Section: Discussionmentioning
confidence: 89%
“…Although it is not clear if hyperhomocysteinemia is a result or a cause of depression induced by stress, many clinical and animal studies indicated that the accumulation of homocysteine has been implicated in the pathogenesis of depression and the increased homocysteine concentration in the plasma might be the result of stress-induced depression [28]. Notably, some reports showed that psychological stress could significantly contribute to high levels of plasma homocysteine [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies would be warranted to assess it. Second, considering that CUMS is also a commonly used animal model for depression (Chengfeng et al 2014), we cannot exclude the interference of emotional effects on cognition in our study. Further studies are necessary to explore the interactions between emotion and cognition, and we would also like to check the role of Hcy in other stress models with fewer components of emotional changes.…”
Section: Discussionmentioning
confidence: 99%